Paradigma Pendidikan dalam Al-Qur`an: Telaah Tafsir Tematik Tentang Tujuan dan Materi Pendidikan - Rayfansyah, Muhammad; Alwizar (Journal of Practice Learning and Educational Development, 2026)
Education in Islam has a strong philosophical foundation derived from the Qur’an as the sacred scripture of Muslims. This study aims to examine in depth the terminology, objectives, and educational content from the Qur’anic perspective. The methodology used is a literature review with a thematic tafsir approach to Qur’anic verses related to education. The findings show that the Qur’an employs various educational terms such as tarbiyah, ta’lim, and ta’dib, each having its own meaning and dimension. The objectives of education in the Qur’an include the formation of a faithful and pious personality, the development of intellectual potential and knowledge, as well as the cultivation of noble character. Meanwhile, the content of education encompasses the teaching of tawhid, worship, ethics, knowledge of the universe, and social skills. This study provides an important contribution to understanding a comprehensive and holistic concept of Islamic education based on the primary source of Islamic teachings.